Penerapan Metode JIGSAW untuk Meningkatkan Pemahaman Siswa SMP Materi Listrik Statis - Unita Sukma Zuliani Nasution; Diah Kesumawati; Azrina Purba; Dini Puji Anggraini (Keguruan, 2023)
This study aims to enhance middle school students' understanding of static electricity material by implementing the jigsaw method. The research was conducted within the context of classroom action research and intended to improve the science learning process concerning the concept of static electricity. Research data were collected using achievement instruments and student learning activity observation sheets, presenting the data as they occurred during the learning process. Actions provided to the research subjects included cooperative learning of the jigsaw type implemented over four cycles. The research stages encompassed action planning, implementation, action observation, and reflection. The research findings indicate that the utilization of the jigsaw method in enhancing the understanding of the static electricity concept in science education has been successful. The improvement in students' understanding of the static electricity concept is evident through the progression of their learning outcomes from Cycle I to Cycle IV.